2013
DOI: 10.1179/1743284712y.0000000118
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electric current pulse on flow behaviour of Al melt in parallel electrode process

Abstract: Electric current pulse (ECP) was commonly applied to solidification process of Al melt to achieve fine solidification microstructure. In this paper, numerical simulation method was employed to analyse flow behaviour of the melt and the mechanism of ECP on the grain refinement during the solidification. The calculation results showed that the ECP led to fluctuation of the Al liquid surface, and the liquid flowed inward and down in a circular motion. The fluctuation and circular flow behaviour were caused by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…It is noted that the experimental SDAS without DC are good agreement with the predicted SDAS curve from the above model. However, the experimental data is remarkably lower than the fitting SDAS when the applied current density is more than 100 A cm -2 , and the relationship between local solidification time and the SDAS with different DC cannot be fitted by equation (4). Under DC of ±200 A cm -2 , the coarsening exponent changes from 1/ 3 toward a value of 0.29.…”
Section: The Relationship Between Sdas and Solidification Parameters ...mentioning
confidence: 91%
See 1 more Smart Citation
“…It is noted that the experimental SDAS without DC are good agreement with the predicted SDAS curve from the above model. However, the experimental data is remarkably lower than the fitting SDAS when the applied current density is more than 100 A cm -2 , and the relationship between local solidification time and the SDAS with different DC cannot be fitted by equation (4). Under DC of ±200 A cm -2 , the coarsening exponent changes from 1/ 3 toward a value of 0.29.…”
Section: The Relationship Between Sdas and Solidification Parameters ...mentioning
confidence: 91%
“…During the solidification of materials, the application of electric current including DC, 2 alternating current 3 and electric current pulse (ECP) 4 has been found to induce significant changes in the structure and properties of materials. Especially, there has been much progress in ECP treatment, and many of the important results are raised by Qin and Bhadeshia in their critical assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Electromagnetic force and flow field in the SPMO treated melt were simulated using ANSYS (a commercial FEM software). 16 Electromagnetic force distribution is shown in Fig. 9.…”
Section: Analysis Of Flow Field In Melt Treated With Spmomentioning
confidence: 99%
“…In 1995, Bamak et al found that the pulse current greatly reduced the eutectic cells of Sn-Pb alloy [3][4][5][6][7]. In recent years, pulsed electromagnetic field has become an emerging technology in the area of electromagnetic coagulation [4,[8][9][10][11][12][13][14][15][16][17]. By fixing the pulse current of an isolated network, Liao et al [18] found that the refining effect was the most remarkable in the nucleation stage.…”
Section: Introductionmentioning
confidence: 99%